Behavioural discrimination of noxious stimuli in infants is dependent on brain maturation. Issue 2 (February 2019) - Green, Gabrielle; Hartley, Caroline; Hoskin, Amy; Duff, Eugene; Shriver, Adam; Wilkinson, Dominic; Adams, Eleri; Rogers, Richard; Moultrie, Fiona; Slater, Rebeccah
Abstract : Abstract: Changes in facial expression are an essential form of social communication and in nonverbal infants are often used to alert care providers to pain-related distress. However, studies of early human brain development suggest that premature infants aged less than 34 weeks' gestation do not display discriminative brain activity patterns to equally salient noxious and innocuous events. Here we examine the development of facial expression in 105 infants, aged between 28 and 42 weeks' gestation. We show that the presence of facial expression change after noxious and innocuous stimulation is age-dependent and that discriminative facial expressions emerge from approximately 33 weeks' gestation. In a subset of 49 infants, we also recorded EEG brain activity and demonstrated that the temporal emergence of facial discrimination mirrors the developmental profile of the brain's ability to generate discriminative responses. Furthermore, within individual infants, the ability to display discriminative facial expressions is significantly related to brain response maturity. These data demonstrate that the emergence of behavioural discrimination in early human life corresponds to our brain's ability to discriminate noxious and innocuous events and raises fundamental questions as to how best to interpret infant behaviours when measuring and treating pain in premature infants. Abstract : Supplemental Digital Content is Available in the Text.Facial expression discrimination between noxious and innocuous stimuli in preterm infants emerges at approximately 33 weeks' gestation and relates to evoked brain activity maturation.